Upaya Mengenalkan Produk UMKM Damar Kurung Melalui Studi Independen Sekolah Ekspor - Jovansa N. K. Dheva; Moch. T. Safirin (Pusat Riset dan Inovasi Nasional, 2024)
Damar Kurung is a typical Gresik city art product and has considerable market and export potential. With the Export School Independent Study program